Pola Pemukiman di Perdesaan dan Perkotaan: Perbandingan dan Faktor yang Mempengaruhi - Novida Yenny; Mulhady Putra; Aisyah Dwi Ramadhani; Nazwa Amelia Putri (Asosiasi Ilmuwan Pendidikan, Sosial, dan Humaniora Indonesia, 2025)
Settlement is a basic human need that is closely related to the feasibility of life and well-being. The purpose of this study is to gain a better understanding of settlement patterns that occur in rural and urban areas, and to investigate the factors that influence these patterns. This study collects, analyzes, and synthesizes related literature. The results show that settlement patterns in urban areas are denser and develop vertically, while settlement patterns in rural areas tend to be spread out and horizontal. Various factors, such as natural conditions (such as climate, topography, water and land availability), socio-economic factors (such as employment, education, and income), and government policies and local cultural developments, influence these differences. These results emphasize that understanding settlement patterns as a whole is essential to building areas that are equitable, sustainable, and responsive to community needs.